Is It Necessary to Photoactivate the Adhesive System Inside Ceramic Laminate Veneers in a Luting Procedure? - Strazzi-Sahyon, Henrico Badaoui [UNESP]; Chimanski, Afonso; Yoshimura, Humberto Naoyuki; Santos, Paulo Henrique dos [UNESP] (Quintessence Publishing Co Inc, 2019)
Purpose: To investigate the need for photoactivation of the adhesive system inside ceramic laminates before the luting procedure and to evaluate the color stability, nanohardness, and elastic modulus of the adhesive interface activated with singlewave and polywave light-curing units. Materials and Methods: A total of 44 lithium disilicate ceramic veneers (7.0 mm x 8.0 mm x 0.6 mm) were fabricated, bonded to enamel, and sorted into four experimental groups (n = 11 each) according to the type of light-curing unit (Radii-Cal [singlewave] or Valo [polywave]) and mode of adhesive system activation (with or without previous photoactivation). Two luting agents were used: the Tetric N- Bond adhesive system and Variolink Veneer resin cement. A visible ultraviolet spectrophotometer was used to evaluate the color stability before and after UVB artificial accelerated aging for 252, 504, and 756 hours (n = 8 samples from each group). A nanohardness tester under a load of 1,000 mu N was used to evaluate the nanohardness and elastic modulus (n = 3 samples from each group). Data regarding the color stability and the mechanical properties (nanohardness and elastic modulus) were subjected to analysis of variance and Tukey protected least significant difference test (alpha =.05). Results: Prior activation of the adhesive system, the distinct light-curing units, and different aging periods exerted no significant difference on the color stability or mechanical properties of the resin cement (P >.05), except for in the group activated with Radii-Cal after 756 hours, in which the nonprevious activation showed lower color alteration compared to the previous photoactivation (P =.0285). Without prior activation of the adhesive with Valo, the polywave unit promoted higher nanohardness and elastic modulus values in the adhesive system (P <.05). Conclusion: In general, singlewave and polywave light-curing units promoted no difference in color stability or the mechanical properties of the adhesive interface. The prior curing of an adhesive system inside ceramic laminate is not necessary.